(untitled) (Altre Modernità, 2018)
Intercultural communication, and particularly tourism translation, means making the cultural values of a given destination accessible to an audience that is not familiar with them. The purpose of tourism information is in fact to negotiate the encounter with the Other, a negotiation involving different stakeholders, the main ones being, on the one hand, translators and intercultural mediators and, on the other, international tourists. In the attempt to provide accessibility to international visitors, qualified as Outsiders, cultural identities will have to be mediated. Translators and intercultural mediators with different degrees of expertise in the field of tourism set themselves the task of translating the foreign into discourse, so as to produce a sense of otherness that will be recognised as different from the familiar. However, this process is extremely delicate, as it undergoes sophisticated stages of linguistic and intercultural transformations. Translators will have to find a balance between an adaptive, naturalising strategy of translation, which makes the foreign destination accessible to Outsiders, and the necessity to maintain a certain authenticity flavour (MacCannell 1976), because cultural diversity, rather than identity, is at the basis of the tourist offer. Translators and mediators will also have to find ways to stimulate the visitors’ curiosity and capture their attention. To this end, translation strategies that go beyond lingua-cultural transfer processes will be discussed, with special attention to models specifically derived from the field of Tourism Studies